Patterns of Failure in Head and Neck Carcinoma of Unknown Primary: Insights from a Tobacco-Associated Cancer Cohort - Laskar, Sarbani Ghosh; Manjali, Jifmi Jose; Budrukkar, Ashwini; Swain, Monali; Dutta, Debanjali; Kumar, Amrendra; Sood, Sahil; Sinha, Shwetabh; Kumar, Anuj; Mohanty, Samarpita; Gupta, Tejpal; Murthy, Vedang; Chaturvedi, Pankaj; Chaukar, Devendra Arvind; Pai, Prathamesh; Pantavaidya, Gouri; Deshmukh, Anuja; Nair, Deepa; Thiagarajan, Shivakumar; Vaish, Richa; Prabhash, Kumar; Joshi, Amit; Noronha, Vanita; Menon, Nandini; Agarwal, Jai Prakash (South Asian Journal of Cancer, 2025)
We report the patterns of failure and survival with carcinoma of unknown primary of the head and neck (CUP-HN).This is a retrospective audit of CUP-HN patients treated with curative radiotherapy (RT) between January 2006 and December 2020. All patients received RT to the neck—definitive RT (DRT) or surgery (Sx) + adjuvant RT (ART), ± chemotherapy.Of the 108 eligible patients, 81 (75%) used tobacco. Positron emission tomography with computed tomography was performed in 102 patients (94.4%). Seventy-five patients (69.4%) were treated with DRT ± chemotherapy, while 33 (30.6%) underwent Sx + ART ± chemotherapy. Median lymph node size was significantly different between DRT and ART groups (5 vs. 3.5cm, p = 0.001). At a median follow-up of 60 months, 35.1% patients had a neck failure (within treatment portal 37, outside portal 1). Nine patients (8.3%) developed 10 sites of subsequent mucosal primary (SMP)—all occurred in the oral cavity, six of whom had received comprehensive mucosal irradiation (CMI). Three-year survival outcomes were significantly better with Sx + ART compared to DRT (local control in neck: 96.8 ± 3.2 vs. 50.6 ± 6.2, p < 0.001, locoregional control: 89.7 ± 5.7 vs. 48.6 ± 6.3, p < 0.001), progression-free survival: 80.7 ± 7.1 vs. 38.7 ± 6, p < 0.001, and overall survival [OS]: 67.2 ± 8.5 vs. 41.9 ± 6.2, p = 0.01), respectively. After propensity score matching, all survival outcomes (except OS) were better with Sx + ART compared to DRT.All SMPs developed in the oral cavity in this tobacco-driven population. Inclusion of oral cavity for CMI may be considered in tobacco-driven populations; however, this has to be weighed against the toxicity involved.
Keywords: unknown primary; cervical lymph nodes; radiotherapy; CUP-HN; head and neck cancer